Implementasi Model Pembelajaran Tutor Sebaya dalam Kelompok Kecil untuk Meningkatkan Hasil Belajar Siswa dalam Menyelesaikan Soal Cerita di SD Negeri 37 Ampenan Kota Mataram - Sariani, Ni Ketut (Jurnal Paedagogy, 2021)
The purpose of this study was to describe the implementation of peer tutoring learning models in small groups to improve student learning outcomes in solving story problems. This research method uses classroom action research which is carried out in three cycles. Each cycle has four stages, namely planning, implementation, observation and reflection. The subjects of the research were the sixth graders of SD Negeri 37 Ampenan which consisted of l9 students. The instruments used are observation and tests, while the data analysis technique uses descriptive analysis. The result of this research is through peer tutor learning model in small groups, students’ skills in solving story problems show good progress which has an impact on increasing student learning outcomes. Based on this study, the learning outcomes obtained by students on the subject of reading pictures or scaled plans increased the average value to around 8.11.